Characterization of Rice Genotypes for SNORKEL1 (SK1) and SNORKEL2 (SK2) Gene - Kumar, Yogendra; Singh, Digvijay; Singh, Shaurya; Sarvjeet, Kumar; Sinha, Sweta (International Journal of Bio-resource and Stress Management, 2023)
The present study was performed in kharif (June-December) 2019 at Bihar Agricultural College, Sabour, Bhagalpur, Bihar, India to screen gene specific markers developed from SNORKEL1 (SK1) and SNORKEL2 (SK2) gene and identify the rice genotypes for the presence of SNORKEL genes. A total of 13 rice genotypes were used out of which 8 genotypes Vaidehi, RYC743, FR13A, Desaria, Dudhi, Birar, Kalaladora and Kajargod indicated the presence of both SNORKEL1 (SK1) and SNORKEL2 (SK2) gene using SK1-1, SK1-2, SK2-1 and SK2-2 markers. Therefore, these genotypes have tolerance ability of deep water flooding due to higher rates of elongation where water stagnates for longer than two weeks. However, results from the present study also revealed that the genotype Desaria and RYC743 had higher rates of elongation and Satyam, Sudha, Purnendu, FR13A, Pansoradhan and Swarna Sub1 had lower shoot elongation rate compared to other genotypes. This study provides gene specific markers for the identification of varieties/donors tolerant to deep water flooding as well as donors to be used in deep water rice breeding programs. Thus, the marker developed and validated in this study will aid rice breeders in quickly and efficiently identifying and introgressing the SNORKEL genes. The results would be a helpful in the development of rice varieties with both submergence tolerance and elongation ability in order to improve the yield stability in flood-prone areas.